2022
DOI: 10.1088/1742-6596/2392/1/012023
|View full text |Cite
|
Sign up to set email alerts
|

Physics Edutainment Learning based on Engklek and Ontang-Anting Games: Creating Fun Physics for Students

Abstract: This study aims to describe students' responses to edutainment-based physics learning. The study was conducted with a qualitative approach involving 33 pre-service physics teachers. The data were analyzed using Miles and Huberman's model, including data reduction, data display, and conclusion drawing. The results showed that 52% of pre-serviceteachers did not know the existence of edutainment-based physics learning as a learning instrument to create exciting and fun physics learning. However, most pre-service … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…This tourist destination in GoFun Bojonegoro is an actual situation, so contextual learning is rarely used in physics learning. Apart from learning new things about physics concepts at the nearby playground, they created a new, fun learning atmosphere (Hariyono et al, 2022). Some previous research confirmed physics concepts in particular playgrounds, such as Batu Night Spectacular (Ariantoro et al, 2021), Indonesian Fantasy World (Choirunnisa' et al, 2021), Lamongan Marine Tourism (Cahyani & Cheng, 2022), and Transmart Surabaya (Indriati et al, 2021).…”
Section: Introductionmentioning
confidence: 98%
“…This tourist destination in GoFun Bojonegoro is an actual situation, so contextual learning is rarely used in physics learning. Apart from learning new things about physics concepts at the nearby playground, they created a new, fun learning atmosphere (Hariyono et al, 2022). Some previous research confirmed physics concepts in particular playgrounds, such as Batu Night Spectacular (Ariantoro et al, 2021), Indonesian Fantasy World (Choirunnisa' et al, 2021), Lamongan Marine Tourism (Cahyani & Cheng, 2022), and Transmart Surabaya (Indriati et al, 2021).…”
Section: Introductionmentioning
confidence: 98%